2015
DOI: 10.3844/ajmsp.2015.21.30
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Meningitis from Patients Suspected of Meningitis Attending Tribhuvan University Teaching Hospital, Kathmandu, Nepal

Abstract: Meningitis is an inflammatory infection of the membranes surrounding the brain and spinal cord, which occurs either as a primary disease or secondarily to disease in some other parts of the body. Its most frequent causes are Neisseria meningitidis, Streptococcus pneumoniae and Haemophilus influenzae. The epidemiological trend of acute meningitis varies with time and geography. Information on the relative frequency of the isolation and antibiotic susceptibility patterns of these pathogens is scarce in Nepal. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…S. pneumoniae , N. meningitidis and H. influenzae were the most commonly reported isolates from bacterial meningitis cases in this study and similar other reports from Nepal [ 19 , 20 , 21 , 22 , 23 ]. Furthermore, meningitis caused by these bacteria are vaccine preventable.…”
Section: Discussionsupporting
confidence: 90%
“…S. pneumoniae , N. meningitidis and H. influenzae were the most commonly reported isolates from bacterial meningitis cases in this study and similar other reports from Nepal [ 19 , 20 , 21 , 22 , 23 ]. Furthermore, meningitis caused by these bacteria are vaccine preventable.…”
Section: Discussionsupporting
confidence: 90%
“…A relatively lower prevalence (2%–2.4%) of cryptococcal meningitis was reported by some researchers of our region 17–19 . Few studies in Nepal have reported cryptococcal meningitis in non‐HIV cases associated with other conditions like liver diseases and prolonged steroid therapy 17,20,21 . However, the proportion of cryptococcal meningitis in PLHIV is higher than in non‐HIV cases.…”
Section: Discussionmentioning
confidence: 57%
“…[17][18][19] Few studies in Nepal have reported cryptococcal meningitis in non-HIV cases associated with other conditions like liver diseases and prolonged steroid therapy. 17,20,21 However, the proportion of cryptococcal meningitis in PLHIV is higher than in non-HIV cases. This might be due to suppression of cell-mediated immunity in PLHIV, which predisposes them for opportunistic infections.…”
Section: Discussionmentioning
confidence: 99%